The Importance of Exclusion of Obstructive Sleep Apnea During Screening for Adrenal Adenoma and Diagnosis of Pheochromocytoma - Alicia C. Weeks MD; Michelle E. Kimple PhD; Dawn Belt Davis MD, PhD (SAGE Publishing, 2015)
Context . As catecholamine elevation is a key element in the diagnosis of pheochromocytoma, more commonplace causes of sympathetic excess, such as obstructive sleep apnea (OSA), should be excluded as standard practice prior to diagnosis. This is essential to avoid misdiagnosis of adrenal incidentalomas identified in the estimated 42 million Americans with OSA, with greater than 4 million projected to undergo a computed tomography study annually. Case Description . A 56-year-old woman presented with a several year history of paroxysmal hypertension, palpitations, and diaphoresis. Abdominal/pelvic computed tomography performed during an unrelated hospitalization revealed a 2-cm left-sided adrenal nodule initially quantified at 37 Hounsfield units. Posthospitalization, 24-hour urine normetanephrine level was markedly elevated. Reassessment 2 weeks later revealed continued normetanephrine excess. Following normal thyroid function tests, morning cortisol, aldosterone, and plasma renin activity, laparoscopic adrenalectomy was performed. Surgical pathology identified an adrenal cortical adenoma. As paroxysms continued postoperatively, repeat 24-hour urine metanephrines were measured, demonstrating essentially unchanged normetanephrine elevation. Search for an alternate cause ensued, revealing OSA with progressive continuous positive airway pressure noncompliance over the preceding year. Regular continuous positive airway pressure therapy was resumed, and at the end of 7 weeks, 24-hour urine normetanephrine levels had declined. Conclusion . Pheochromocytomas are rare and sleep apnea is common. However, the overlap of clinical symptoms between these disorders is substantial, as is their ability to produce catecholamine excess. Thus, excluding uncontrolled or undiagnosed OSA in high-risk patients should be standard practice before diagnosing pheochromocytoma.